Case Report of a solitary benign spindle cell tumor in the deep thigh - Zhang, Haokang; Yang, Xinhua; Li, Guishi (Frontiers in Surgery, 2026)
ObjectiveThis study aims to investigate the clinicopathological characteristics, imaging features, diagnostic approaches, and treatment strategies of spindle cell tumors of the thigh.MethodsWe performed a retrospective analysis of the clinical data of a patient admitted to the Department of Orthopedics at Yantai Yuhuangding Hospital in 2025. The study period encompassed the preoperative assessment, surgical intervention, and a 10-month postoperative follow-up.ResultsA 61-year-old male patient was admitted to our hospital with a 1 year history of right thigh pain without an obvious cause, accompanied by restricted mobility. Physical examination revealed a mass in the mid-posterior region of the right thigh with indistinct borders and skin numbness. Tenderness and percussion pain were noted in the right thigh, with pain limiting flexion and extension. Internal rotation was preserved, whereas external rotation was restricted. The Lasegue sign was positive. MRI examination showed a soft tissue mass located posteromedial to the proximal-to-mid segment of the right femur, raising suspicion for a tumor. The mass was irregular and lobulated with indistinct borders, presenting irregular, slightly prolonged signals on T1-weighted images and mixed high-/low-intensity signals on T2-weighted images. Intraoperatively, the tumor was located in the semimembranosus and semitendinosus muscles, spreading medially toward the anterior thigh. The tumor exhibited indistinct borders, lacked a capsule, and compressed the sciatic nerve. The tumor measured approximately 10 cm×5.6 cm×23 cm. Postoperative histopathological examination confirmed the diagnosis of a spindle cell tumor (occupying lesion of the root of the right thigh). The patient's postoperative pain and numbness were significantly alleviated.ConclusionSolitary spindle cell tumors arising in the deep soft tissues of the thigh are clinically uncommon and often lack features related to neurofibromatosis type I (NF1). MRI is an important preoperative diagnostic modality. Complete surgical excision remains the treatment of choice and offers a good prognosis.